Marburg virus disease outbreak amidst COVID-19 in the Republic of Guinea: A point of contention for the fragile health system? - Osaretin Christabel Okonji; Emeka Francis Okonji; Parvathy Mohanan; Maryam Salma Babar; Amna Saleem; Uzzam Ahmed Khawaja; Mohammad Yasir Essar; Mohammad Mehedi Hasan (Elsevier, 2022)
In August 2021, the Marburg virus disease (MVD) outbreak was confirmed amid the coronavirus disease 2019 (COVID-19) pandemic in the Republic of Guinea. This is the first time it is detected in Guinea and West Africa. Marburg virus is one of the world's most threatening diseases, causing severe haemorrhagic fever, with a case fatality rate of 90%. Currently, there are no vaccines and specific antiviral drugs for MVD. Technical teams and community health care workers that were set up as part of the recent Ebola virus disease (EVD) outbreak that was declared over on June 19, 2021, are now redeployed to support governments response activities of the MVD outbreak in the country. The MVD is an added burden to the fragile healthcare systems that are already overburdened with multiple reoccurring epidemics and the COVID-19 pandemic. Previous epidermic strategies are needed to contain the spread of the disease, amid the COVID-19 pandemic, so the health care systems are not overwhelmed. This commentary discusses the available evidence regarding the epidemic of MVD in Guinea amid the COVID-19 pandemic, and highlights the efforts, challenges to be prioritized, and provides evidence-based recommendations.